Corporate governance practices and companies' R&D orientation: Evidence from European countries - Florence Honoré; Federico Munari; Bruno van Pottelsberghe de la Potterie (Bruegel, 2011)
This paper empirically investigates if corporate governance practices affect the resources firms devote to R&D. Two databases - one on governance ratings and the other on R&D intensity - are merged to obtain a multi-country, multi-sector sample of 279 European companies involved in R&D activities. The relationship is found to be negative: a higher governance score correlates with lower R&D intensity. An executive remuneration system that is linked to the firm's financial performance has a particularly strong negative impact on R&D. This confirms the hypothesis that incentive mechanisms lead managers to focus on more predictable and easily measurable short-term activities, ultimately hampering the commitment to innovative projects. Other factors include the equal treatment of shareholders, the absence of anti-takeover devices and severance pay.
Keywords: O31; O32; O33; G34; 330; R&D intensity; corporate governance; remuneration; shareholder rights; Corporate Governance; Betriebliche Forschung; Managervergütung; EU-Staaten